The Determinant Factors of Research and Publication Information System Use Behavior in Private University at Surabaya: The Moderating Role of Service Quality - Padmawidjaja, Liestya; Salim, Ika Raharja; Radianto, Wirawan Endro Dwi (Journal The Winners, 2024)
The development of an information system in the Research and Community Development Department in one of the private universities in Surabaya, which has already been developed since 2020, has not yet undergone an evaluation of user acceptance, specifically among the faculty. Furthermore, the satisfaction survey conducted has been too general so far, making it essential to evaluate the service quality of the information system provided. The research aimed to analyze user acceptance of X information system from the Research and Community Development Department. Additionally, it seeked to assess its service quality. The empirical research was quantitative by design, and data were collected from 228 faculty members. The research model was analyzed using PLS-SEM. The data analysis results indicate that all items used in the research are valid and reliable, with cross-loading values ranging from 0.837 to 0.980. Then, the Cronbach’s alpha values are greater than 0.6. It is found that out of six proposed hypotheses, four hypotheses are accepted and two hypotheses are rejected. The research finds that ease of use and usefulness influence intention to use, which increases usage behavior. The research also shows that service quality does not moderate the influence of perceived usefulness and ease of use on intention to use.